There are no Communists Here: Workers, Elites, and Political Power in Ciudad Juárez during the 1930s - Hijar, Andrés (Mexican Studies/Estudios Mexicanos, 2021)
Abstract: Workers’ unions and political projects in postrevolutionary Chihuahua, specifically the border city of Ciudad Juárez, have remained largely unexamined by historians. Existing research in this state has mainly focused on the role of political and economic elites. In this article, I examine the rise of a radical labor wing spearheaded by the communist-leaning Cámara Sindical Obrera in the political, social, and economic milieu on the border throughout the 1930s. This wing encouraged a sense of internationalism and mass direct action. Once the Cárdenas regime ended, workers experienced significant setbacks at both the national and local levels. Scholars examining workers’ movements during the same period have identified divisions within the labor movement as the main reason behind the demise of communist unions within organized labor. I argue that the gradual co-optation of the radical wing of the labor movement, beginning in the 1940s, had more to do with the violence perpetrated against these unions by emergent statewide elites than with fractures within the movement. I demonstrate that violence, arrests, and outright murder of key leaders weakened communist unions by altering their internal mechanisms designed to remain independent. In this difficult context, organized labor responded to the challenge with different degrees of success.
Code: Mexican Studies/Estudios Mexicanos
Keywords: Business history in the Iberian Peninsula